Chronic intensive care‐related pain: Exploratory analysis on predictors and influence on health‐related quality of life. (5th November 2017) - Baumbach, P.; Götz, T.; Günther, A.; Weiss, T.; Meissner, W.
Abstract: Background: There is growing evidence for the development of chronic pain after intensive care. Nonetheless, there is only limited knowledge about factors leading to chronic intensive care‐related pain (CIRP). Thus, the primary objective was the identification of predictors of CIRP. Moreover, we aimed to assess the impact of CIRP on patients' health‐related quality of Life (HRQOL). Methods: Comprehensive information on patients' pain before ICU admission and present pain was collected longitudinally by means of the German Pain Questionnaire 6 and 12 months after ICU discharge (ICUDC ). In addition, a subsample of patients underwent Quantitative Sensory Testing (QST). We used Generalized Estimating Equations to identify predictors of CIRP with logistic regression models. Results: In total, 204 patients (197/159 at 6/12 months after ICUDC ) were available for the analyses. In the multivariate models, moderate to severe average pain in the 4 weeks after ICUDC, lower age, female sex, increased inflammation and chronic pain conditions and increased levels of anxiety before ICU admission were predictive for CIRP. In addition, small fibre deficits and lower disease severity were associated with CIRP in the QST subsample (81 patients, 77/55 at 6/12 months after ICUDC ). Patients with CIRP reported significantly lower HRQOL than patients without CIRP. Conclusions: Chronic intensive care‐related pain is associated with specific decrements in HRQOL. Knowledge about the identified predictors is of clinical and scientific importance and might help to reduce the incidence of CIRP. Significance: Chronic intensive care‐related pain is associated with specific decrements in health‐related quality of life. While most of the identified predictors for CIRP can only be considered as risk factors, especially adequate (post‐) acute pain management should be studied as preventive strategy.